2018
DOI: 10.21873/invivo.11142
|View full text |Cite
|
Sign up to set email alerts
|

Expand+In Vivoiv.iiarjournals.orgIn Vivo September-October 2017 vol. 31 no. 5 877-884 Antrodia Cinnamomea Reduces Carbon Tetrachloride-induced Hepatotoxicity In Male Wister Rats

Abstract: Abstract. Background/Aim: Antrodia cinnamomea is foundwith polysaccharides, lipids, vitamins, fibers and ash (minerals)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It has been reported that lipid peroxidation, reducing activity of antioxidant enzymes, and generation of free radicals are the primary reasons of CCl 4 -induced hepatic injury [ 38 ]. Previous studies have already shown that one of the main causes of CCl 4 -induced hepatotoxicity is the generation of lipid peroxides by free radical derivatives of CCl 4 [ 39 ]. Thus, the antioxidant activity or the inhibition of the generation of free radicals could be one of the mechanisms in the protection against CCl 4 -induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that lipid peroxidation, reducing activity of antioxidant enzymes, and generation of free radicals are the primary reasons of CCl 4 -induced hepatic injury [ 38 ]. Previous studies have already shown that one of the main causes of CCl 4 -induced hepatotoxicity is the generation of lipid peroxides by free radical derivatives of CCl 4 [ 39 ]. Thus, the antioxidant activity or the inhibition of the generation of free radicals could be one of the mechanisms in the protection against CCl 4 -induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%